2021
DOI: 10.3389/fphar.2021.759095
|View full text |Cite
|
Sign up to set email alerts
|

The Microbiota in Systemic Lupus Erythematosus: An Update on the Potential Function of Probiotics

Abstract: Systemic lupus erythematosus (SLE) is a kind of chronic diffuse connective tissue illness characterized by multisystem and multiorgan involvement, repeated recurrence and remission, and the presence of a large pool of autoantibodies in the body. Although the exact cause of SLE is not thoroughly revealed, accumulating evidence has manifested that intake of probiotics alters the composition of the gut microbiome, regulating the immunomodulatory and inflammatory response, which may be linked to the disease pathog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 132 publications
(197 reference statements)
0
28
0
8
Order By: Relevance
“…In agreement with previously published results using 16S sequencing ( 10 , 13 ), we observed a decrease in the diversity of SS patient gut microbiota relative to healthy controls that correlates with ocular disease severity. Decreased microbial gut diversity has been observed in other autoimmune diseases including systemic lupus erythematosus (SLE) and rheumatoid arthritis ( 43 45 ). We observed that the decrease in diversity is accompanied by shifts in the composition of the community, with depletion of specific microbes that may be protective of the ocular surface, including several Bacteroides species.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with previously published results using 16S sequencing ( 10 , 13 ), we observed a decrease in the diversity of SS patient gut microbiota relative to healthy controls that correlates with ocular disease severity. Decreased microbial gut diversity has been observed in other autoimmune diseases including systemic lupus erythematosus (SLE) and rheumatoid arthritis ( 43 45 ). We observed that the decrease in diversity is accompanied by shifts in the composition of the community, with depletion of specific microbes that may be protective of the ocular surface, including several Bacteroides species.…”
Section: Discussionmentioning
confidence: 99%
“…Some probiotics, such as Lactobacillus , can restore dysbiosis and enhance intestinal barrier function and alleviate SLE symptoms. Data supports that probiotics may restore the abnormal T cell subsets, particularly the abnormal levels of naïve CD4+T, γδT, Tfh, Treg, and Th17 cells seen in SLE [ 74 ]. In a recent meta-analysis, probiotics reduced inflammation in patients with RA, measured with C-reactive protein levels [ 75 ].…”
Section: Potential Microbiome Therapeutics For Ctd-ild and Vasculitismentioning
confidence: 88%
“…Animal studies have shown that probiotics could modify various immune parameters, such as the innate immune response of macrophages and dendritic cells [ 35 ], and the cell wall structure of probiotic Lactobacillus casei could potently induce IL-12 production [ 36 ]. In contrast, animal studies suggested that intake of Lactobacillus casei Shirota could alleviate SLE symptoms and their cardiovascular and renal complications [ 37 ]. More research is required to establish the safety and efficacy of probiotics for the prevention and treatment of photosensitivity in patients with SLE.…”
Section: Discussionmentioning
confidence: 99%